PENGELOLAAN KOLEKSI MULTIMEDIA PADA PERPUSTAKAAN: STUDI KASUS DI PERPUSTAKAAN UPT BALAI INFORMASI TEKNOLOGI LIPI - Kamaludin . (Perpustakaan IPB, 2014)
ABSTRACT Advances in information and communication technology these days has affected to the library's collection. Today’s [U1] library collection is not only in printed media such as books and journals but also in the non printed media. As these changes, this study aims to determine the management of multimedia collections in Technical Implementation Unit for Technological Informasion Division - Indonesian Institute of Sciences' library. From the reserach results revealed that the multimedia collection owned by the libraries is 208 titles. The procurement of multimedia collection is done by self-producing. Multimedia collection processing has been carried out in accordance with cataloging rules, but to date this research, the number is still as many as 117 titles. For further purpose, a video corner has been provided, for the visitors play the collection of packaging VCD/DVD with a video player. There is no lending policies of multimedia collection to be taken home by the visitors. Keywords : Library, procurement, processing, services, multimedia collection. [U1] Sudah diperbaiki